ASSESSING STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION THROUGH PROBLEM BASED LEARNING MODEL (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2021)
This research was focused on points whether (or not) the effect of Problem Based Learning with Webtoon on students’ reading comprehension of the SMA Negeri 6 Enrekang Class X. This research applied experimental design that treats only one group. The population of the research was the students of SMA Negeri 6 Enrekang Class X. In determining the sample, the researcher used simple random sampling technique. The research instruments were reading test and questionnaire. Then, the data was analyzed by using scoring rubric for reading test. And also, to measure the students’ interest, the researcher used SPSS application verse 23.0.The result of the research showed that there was a worth enhancement of the students’ achievement in pre-test and post-test. The mean score reached 79.80 at the post-test with standard deviation 7.94. It is very different with the pre-test result, where more than 50% students get score under the KKM. The effect of Problem Based Learning with Webtoon gives a positive interest toward students to learn reading comprehension, mainly for narrative text. The learning process was alive and the students were passionate. Besides, the students were more enthusiastic because the story in Webtoon is served by colorful and interactive pictures. As the conclusion, the effect of the Problem Based Learning with Webtoon assisted the students in comprehend the text in reading learning. By the internet connection, the application of Webtoon for reading learning make the students were easier to learn every time.